2021
DOI: 10.1162/netn_a_00177
|View full text |Cite
|
Sign up to set email alerts
|

Computerized physical and cognitive training improves the functional architecture of the brain in adults with Down syndrome: A network science EEG study

Abstract: Understanding the neuroplastic capacity of people with Down syndrome (PwDS) can potentially reveal the causal relationship between aberrant brain organization and phenotypic characteristics. We used resting-state EEG recordings to identify how a neuroplasticity-triggering training protocol relates to changes in the functional connectivity of the brain’s intrinsic cortical networks. Brain activity of 12 PwDS before and after a 10-week protocol of combined physical and cognitive training was statistically compar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 87 publications
1
6
0
Order By: Relevance
“…In this study, within-cohort and between-group differences in SWLS and GSE at two time points, pre-and post-intervention, were analysed. At baseline, and in line with previous work in this domain [26], all participants indicated they were satisfied (score of [26][27][28][29][30] or extremely satisfied (score of [31][32][33][34][35] with life, but there were no statistically significant changes in SWLS from pre-to post-intervention in the total sample or within any of the groups. GSE was below the international average of 29.55 [34] at baseline, but scores in the total sample improved significantly to above average throughout the duration of the study.…”
Section: Life Satisfaction and Self-efficacysupporting
confidence: 68%
See 1 more Smart Citation
“…In this study, within-cohort and between-group differences in SWLS and GSE at two time points, pre-and post-intervention, were analysed. At baseline, and in line with previous work in this domain [26], all participants indicated they were satisfied (score of [26][27][28][29][30] or extremely satisfied (score of [31][32][33][34][35] with life, but there were no statistically significant changes in SWLS from pre-to post-intervention in the total sample or within any of the groups. GSE was below the international average of 29.55 [34] at baseline, but scores in the total sample improved significantly to above average throughout the duration of the study.…”
Section: Life Satisfaction and Self-efficacysupporting
confidence: 68%
“…The suite of games was selected after conducting a pilot study and was adjusted for each participant if the participant presented with a visual and/or auditory impairment [9]. This form of computerised training has previously been validated in a population with DS [29]. A third group of participants was instructed to implement the combined (COM) walking and cognitive training exercises for eight weeks, whilst a final group of participants was required to maintain their normal day-to-day-life and not partake in an intervention, therefore acting as a control group (CON) with a pseudo-intervention period of eight weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Inherent obstacles of those methods include data loss, subjectivity bias, difficulty in synchronous monitoring at different settings, real-time recognition, and interpretation of behavior (Davila-Montero et al, 2021;Pandria et al, 2022). For addressing the limitations of existing approaches, we have designed and implemented a bundle of tools over the past few years, namely, the WHAAM application (Spachos et al, 2014), the ADHD360 (Pandria et al, 2022) platform, and the AffectLecture application (Siouli et al, 2017(Siouli et al, , 2020, in addition to exploiting the commercially available platform BrainHQ (Romanopoulou et al, 2017;Anagnostopoulou et al, 2021;Romanopoulou et al, 2021) setting different goals and targeting different populations. The WHAAM application enables the digital monitoring of Attention Deficit Hyperactivity Disorder (ADHD) behavior as well as the planning of an intervention and the statistical evaluation of its effectiveness (Spachos et al, 2014;Merlo et al, 2018) while the ADHD360 stands for an integrated platform that includes a serious game for early detection of ADHD characteristics and a mobile application for behavior monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…The exergame platform of Long Lasting Memories Care has proven to significantly improve strength, flexibility, endurance, and balance in older adults [ 20 ]. Furthermore, a previous study conducted by Konstantinidis et al [ 21 ] demonstrated the value of in-game metrics generated from body movement interactions with the exergame for detecting cognitive decline, and the study by Anagnostopoulou et al [ 22 ] demonstrated evidence of improving the functional architecture of the brain in adults with Down syndrome.…”
Section: Introductionmentioning
confidence: 99%